Recommendations for general surgery activities in a pandemic scenario (SARS‐CoV‐2). Issue 9 (23rd April 2020) - Di Marzo, F.; Sartelli, M.; Cennamo, R.; Toccafondi, G.; Coccolini, F.; La Torre, G.; Tulli, G.; Lombardi, M.; Cardi, M.
Abstract : Challenging times